Structural Changes in the Growth of the Malaysian Manufacturing Sector from 1970-2000 - Kamaruddin, Rohana (2006)
The manufacturing industry has been an important sector in the Malaysian economy for the past three decades. The important role of this sector is due not only to the fact that Malaysia today depends substantially on manufacturing for its foreign exchange earnings, but also because Malaysia is the main exporter of electrical and electronic products. This study examined the sources of structural changes in output growth of Malaysia's economy over the 1978-2000 period, through analysis of the demand side using the 1978, 1991 and 2000 input- output tables. This study also analysed changes in the value-added growth patterns of the manufacturing sector over the period from 1970 to 2000. Two approaches were employed in this study, the econometric approach using UECM (unrestricted error correction model) and the structural decomposition analysis (SDA) approach. The econometric approach was used to determine the long-run relationships between the value-added of manufacturing, per capita income, population and export. The second method, the structural decomposition analysis, was used to analyse the sources of growth and key sectors in the manufacturing industry. Introduction of the export-oriented strategy in the 1970s and 1980s to replace the import substitution strategy gave fresh impetus to industrial growth. This was evidenced in the long-run movement in export and the value-added of the manufacturing sectors. As the results show, most of the industries were non-resource based such as textiles, electrical and electronic products, which was in line with the world's increasing demand for these products. Export followed by domestic consumption is increasingly an important factors of change in the industrial growth patterns for the Malaysian economy. The second part of the study employed the input-output analysis. The analysis computed the compositional structural change as a result of decomposition. The study found that the Malaysian economy had undergone a number of structural changes, caused mainly by the reorientation of industrialization strategies as well as by variations in the composition of domestic demand. The results of the analysis indicate that during the second half of the OPPl (First Outline Perspective Plan) period between 1978 and 1991, domestic demand expansion in the agriculture, light industries, heavy industries, mining and services sectors was the dominant source of growth in the economy. However, in the comparison between domestic expansion and export expansion, domestic demand expansion was still dominating in all these sectors. From 1991 to 2000, the growth in the mining and heavy industries sectors was due mainly to export expansion. Surprisingly, the light industries sector experienced a negative growth during this period, while the agriculture and services sectors showed declining growth trends. For the entire period between 1978 and 2000, export expansion appeared to be the dominant source of growth for the heavy industries and mining sectors, slightly higher in percentage than the domestic demand expansion. The third part of the study employed the Rasmussen (1956) degree of dispersion index using the input-output table. The findings indicate that the key sectors in 1978, 1991 and 2000 were livestock, grain mills, rubber products and basic metal industries. The combined results of the sources of growth and key sectors in the year 2000 reveal that domestic demand expansion accounted for most of the growth of the key sectors.